Upaya Meningkatkan Motivasi dan Hasil Belajar Materi Tema 2 Melalui Model Pembelajaran Talking Stick Pada Siswa Kelas VI SDN Tanjungsari - Marni Marni (Al Hikmah: Journal of Education, 2020)
The purpose of this research is to describe the learning process of the Talking Stick model in learning Theme 2 Sub-theme 2 Learning 6, to find out whether the Talking Stick model can increase student learning motivation, and to find out whether the Talking Stick model can improve student learning outcomes of Class VI SDN Tanjungsari. This research method uses classroom action research. The research subjects were students of class VI SD Negeri Tanjungsari, Jakenan District, Pati Regency. The research procedure was carried out in 2 cycles of action. The results of the research in cycle I obtained an average value of 2.50 in the sufficient category, student learning motivation obtained an average score of 69 in the sufficient category, and completeness of the learning outcomes was 73% with an average value of 78. In the second cycle, it increased to an average value. 3.29 with a very good category, student learning motivation increased to 88 in the good category, while the completeness of student learning outcomes was 92% with an average score of 88.Tujuan dari penelitian ini yaitu untuk mendeskripsikan proses pembelajaran model Talking Stick pada pembelajaran Tema 2 Subtema 2 Pembelajaran 6, untuk mengetahui apakah melalui model Talking Stick dapat meningkatkan motivasi belajar siswa, dan untuk mengetahui apakah melalui model Talking Stick dapat meningkatkan hasil belajar siswa Kelas VI SDN Tanjungsari. Metode penelitian ini menggunakan Penelitian tindakan kelas. Subyek penelitian yaitu siswa kelas VI SD Negeri Tanjungsari  Kecamatan Jakenan Kabupaten Pati. Prosedur penelitian dilaksanakan dalam 2 siklus tindakan. Hasil penelitian siklus I memperoleh nilai rata 2,50 dengan kategori cukup, motivasi belajar siswa memperoleh nilai rata-rata yaitu 69 dengan kategori cukup, dan ketuntasan hasil belajar 73% dengan nilai rata-rata 78. Pada siklus II meningkat menjadi nilai rata-rata 3,29 dengan kategori sangat baik, motivasi belajar siswa meningkat menjadi 88 dengan kategori baik, sedangkan ketuntasan hasil belajar siswa 92% dengan nilai rata-rata 88.